Analisis Pengaruh Program Laku Pandai terhadap Pertumbuhan Dana Pihak Ketiga (DPK) - Taufiq Andre Setiyono; Sri Suharti (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
Based on the Financial Literacy and Inclusion Survey of 250 million Indonesians, the level of financial literacy has only reached 29,70%. The public has not used financial services, especially banking due to limited access from the bank, which will know the administrative costs, and the requirements are considered complicated. However, on the other hand, banking as an intermediary institution is required to provide adequate service access that can be easily accessed by all type of society. This program aims to absorb funds from people who have not been reached by bank offices, so that rural communities can enjoy financial service facilities without having go to the bank. The purpose of this research is to obtain empirical evidence of the effect of Laku Pandai program’s to the funds collected from people (third party funds). In this research, the data used secondary data sourced from IDX. Data collected by documentation is recording documents related with this research, as well as literature study is reviewing the various of literatures that support this research. The data analysis technique used quantitative methods. Tabulation and statistical analysis technique used different test analysis technique t-test.